Structural and electrical behaviour in Bi14YO22.5. Issue 101 (1st October 2015) - Struzik, M.; Malys, M.; Krynski, M.; Wojcik, M.; Dygas, J. R.; Wrobel, W.; Krok, F.; Abrahams, I.
Abstract : Ab initio molecular dynamics calculations show low energy barriers for oxide ion conduction along c -axis channels in βIII -Bi14 YO22.5 . Abstract : Structure and electrical conductivity in the oxide ion conducting compound Bi14 YO22.5 have been investigated by powder X-ray and neutron diffraction, a.c. impedance spectroscopy, measurements of transference number and ab initio molecular dynamics (MD) simulations. Phase behaviour was studied using variable temperature X-ray diffraction and differential thermal analysis. The structure at room temperature is of the βIII tetragonal-type, details of which are discussed, including its relationship to both β and δ phases of Bi2 O3 . Bi14 YO22.5 undergoes a reversible phase transition to a cubic δ-Bi2 O3 type phase at high temperatures. This phase exhibits very high electrical conductivity, with transference numbers indicating that this conductivity is almost purely ionic in nature. MD simulations confirm 3-dimensional oxide ion transport in the βIII -phase.